The effects of interactive mini-lessons on students' educational experience - Lindsay D. Richardson (Association for Learning Technology, 2023)
With the shift to online learning, many instructors have been forced into course delivery that involves educational lecture videos. There are a number of different elements that impact the quality of educational videos and overall student experience (e.g. instructor eye gaze, audio levels, screen sizing). More specifically, research has demonstrated that segmented videos have educational benefits over the traditional didactic ones. The present experiment aimed to examine whether interspersed interactive content could increase post-secondary students' retention and engagement above simple segmentation. As such, young adults experienced one of four lesson types: didactic video, segmented videos, segmented videos with interactive content, and a condensed version of the interactive segmented videos. Then, they were asked to complete an engagement scale, an online learning experience questionnaire, and a surprise test. The results demonstrated a performance benefit to segmented videos for post-secondary students who prefer to learn in person as opposed to online.